The anonymous collective and the network/conspiracy of genres: plural subjectivations and intertextuality in 1960’s Brazil (Per Musi, 2014)
This paper highlights the scarcely understood plurality of genres in 1960s MPB and Tropicália, correlating it to the decade’s upheavals. In this ethnomusicological research, music genres were taken as discourses, and different genres were perceived as the discourses of different social and cultural groups. Investigating this phenomenon through the concept of intertextuality, I analyzed how cultural identities built around delimited genres were deconstructed by the rupture of the frontiers between genres.